Lumped Parameter Thermal Modelling of Electric Machines - Anderssson, Björn (My University, 2013)
Two thermal resistance network models have been developed for the steady state radial heat ow an experimental IPMSM. The models have been based on published material, but also on some case studies with the purpose of determining the best choice of methods for certain situations. In one case study on hollow cylinders, it is concluded that it is favourable to place nodes with heat sources representing evenly distributed losses in a point corresponding to the mean radius of the object, rather than the resistive midpoint. Furthermore it is investigated whether the accuracy of a thermal resistance network model can be improved by increasing the resolution of the node configuration. The result indicates that so is the case, although with some ambiguity. The increased complexity of the high resolution network makes it more bulky however, which is a disadvantage compared to the low resolution node configurations. The two network models are used to analyse the IPMSM, and compared with a FEM model made in ANSYS Mechanical. A number of parameters are swept to investigate the machines dependency on some thermally important design characteristics, and also the sensitivity to errors from uncertain input data, geometry approximations, and other estimations. Such uncertain parameters are e.g. the interface gaps between machine components, the turbulence model in the air gap, and the thermal model of the slots. Regarding the design aspects, it is suggested to strive towards minimising the contact gaps during the assembly, and consider the choice of materials used in the stator slots.
Keywords: Elkraftteknik; Electric power engineering